Fatty acid composition of milk from Holstein x Gyr cows grazing on marandu grass supplemented with concentrate containing sunflower oil - Bárbara Cardoso da Mata e Silva (Semina: Ciências Agrárias, 2018)
The inclusion of plant oils in the diets of grazing cows represents a promising nutritional strategy for the production of milk naturally enriched with bioactive compounds, such as rumenic (cis-9, trans-11 CLA), vaccenic (trans-11 C18:1) and oleic (cis-9 C18:1) acids. The aim of this study was to evaluate the effect of dietary supplementation with sunflower oil (SO) on the fatty acid (FA) composition of milk from Holstein x Gyr dairy cows grazing on Urochloa brizantha cv. Marandu under rotational stocking. Sixteen multiparous cows with 185±10 days in milk received a concentrate containing 0% (control) or 15% SO on a dry matter basis in a randomized block design with two replications (paddocks). The results were analyzed with mixed models (P≤0.05) using repeated measurements over time, as represented by sampling days 14, 35 and 62 (periods 1, 2 and 3, respectively). In any period, an effect of SO supplementation was observed on milk production, pasture dry matter intake and nutrients intake, whereas the concentrations of most milk FA were altered in SO-fed cows. In particular, dietary supplementation with SO resulted in the production of milk enriched with FA beneficial to human health (rumenic, vaccenic and oleic acids) and with lower levels of hypercholesterolemic lauric (C12:0), myristic (C14:0) and palmitic (C16:0) acids. This positive effect on the nutritional quality of milk fat was more noticeable from the 40th to 43rd days of sunflower oil supplementation.